A soluble starch synthase I gene, IbSSI, alters the content, composition, granule size and structure of starch in transgenic sweet potato - Yannan Wang (Nature Portfolio, 2017)
Abstract Soluble starch synthase I (SSI) is a key enzyme in the biosynthesis of plant amylopectin. In this study, the gene named IbSSI, was cloned from sweet potato, an important starch crop. A high expression level of IbSSI was detected in the leaves and storage roots of the sweet potato. Its overexpression significantly increased the content and granule size of starch and the proportion of amylopectin by up-regulating starch biosynthetic genes in the transgenic plants compared with wild-type plants (WT) and RNA interference plants. The frequency of chains with degree of polymerization (DP) 5–8 decreased in the amylopectin fraction of starch, whereas the proportion of chains with DP 9–25 increased in the IbSSI-overexpressing plants compared with WT plants. Further analysis demonstrated that IbSSI was responsible for the synthesis of chains with DP ranging from 9 to 17, which represents a different chain length spectrum in vivo from its counterparts in rice and wheat. These findings suggest that the IbSSI gene plays important roles in determining the content, composition, granule size and structure of starch in sweet potato. This gene may be utilized to improve the content and quality of starch in sweet potato and other plants.